Pengaruh Lapisan Kalsium pada Devais Sel Surya Organik Berbasis Bahan Polimer - Budiawan, Widhya; Widodo, Slamet (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
Organic solar cells (OSC) as an emerging photovoltaics devices have potential clean energy source due to their advantages properties, including low-cost production, light weight, and promising for flexible devices. In this study, we investigated the effect of calcium as buffer layer on top photoactive layer of the polymer based solar cell device. Poly-3-hexylthiophene (P3HT) as donor material combining with phenyl-C61-butyric acid methyl ester (PC61BM) were blended to form bulk heterojunction. Calcium was deposited on top of polymer (P3HT) and fullerene derivative (PC61BM) photoactive layer using thermal evaporation inside ultrahigh vacuum chamber. Calcium was selected as buffer layer because of its low-work -function in order to improve performance of polymer solar cells. Our study presented that calcium buffer layer enhanced the performance of solar cells mainly in open circuit voltage, VOC, (0.45 V to 0.61 V) and fill factor, FF, (44% to 65%), increasing power conversion efficiency (PCE) from 1.79% to 3.79%. This result suggested that the improvement of polymer solar cells performance because of the recombination suppression and more efficient charge transfer in cathode. The energy level alignment and work function properties of calcium form an ideal ohmic contact between the active layer and the cathode, thus ensuring effective electron injection from the active layer to the cathode. We also demonstrated the fabrication of polymer solar cells device under ambient atmosphere. However, the devices fabricated under ambient atmosphere have lower performances than fabricated inside nitrogen filled glovebox, because polymer photoactive material and calcium are easily degraded by moisture.